Cardiovascular toxicity of antitumor therapy: effect on myocardial and vascular remodeling - Yu. Yu. Kirichenko; I. S. Ilgisonis; T. V. Ivanova; A. S. Zolotukhina; N. V. Khabarova; E. V. Privalova; Yu. N. Belenkov (Кардиоваскулярная терапия и профилактика)
Aim. To study the effect of multiagent chemotherapy on structural and functional vascular, electrophysiological parameters and cardiac hemodynamics in patients with stomach cancer.Material and methods. The study included 3 groups of 25 people: healthy volunteers, those with established cardiac disease (hypertension + coronary artery disease), gastric adenocarcinoma (fluoropyrimidine/platinum-based chemotherapy). Cancer patients before and after chemotherapy courses underwent non-invasive assessment of vascular wall and endothelial dysfunction (videocapillaroscopy, digital photoplethysmography), as well as electrocardiography and echocardiography. Healthy volunteers and cardiac patients were examined once.Results. In cancer patients, even before chemotherapy courses, endothelial dysfunction (ED) (occlusal index, 1,7 (1,4; 1,9), normal values >1,8) and structural vascular disorders (stiffness index, 8,9 m/s (7,7; 9,7), normal values <8 m/s; refractive index, 32,4% (27,5; 37,7), normal values <30%). All above-mentioned parameters significantly worsened after multiagent chemotherapy (progression of ED and vascular wall remodeling: occlusal index, 1,3 (1,2; 1,5) (p<0,0002); stiffness index, 10,3 m/s (9,5; 11,2) (p<0,0001); reflection index, 40,2% (35,5; 43,6) (p<0,001) Decrease in left ventricular ejection fraction and diastolic function was detected. The number of supraventricular and ventricular premature beats during chemotherapy increased 9 and 10 times, respectively (p<0,05).Conclusion. The study for the first time assessed the effect of multiagent chemotherapy on ED, vascular stiffness and cardiac hemodynamics in patients with gastric cancer. A significant aggravation of all endothelial function parameters after treatment has been proven, which requires further study in order to develop criteria for early cardiovascular toxicity.